Ser filho sacrílego na Colônia: cartas de legitimação no Rio de Janeiro setecentista - Papa, Sarah Kelly Limão (2020)
The aim of this work was to contribute to the studies of illegitimate offspring in eighteenthcentury Portuguese America, by describing a procedure of legitimization of the spurious sons of priests, called sacrileges. The methodology used was initially bibliographic, using the most current legal and historical literature on the subject, as well as laws and doctrines of the period, such as the Philippine Ordinances, the First Constitutions of the Archbishop of Bahia and the 18th century jurisconsult Pascoal José de Melo Freire. This way, it was offered an overview of the Old Regime of the Portuguese Empire, the Colonial Law, the Tridentine clergy and the family on both sides of the Atlantic. After that, it was adressed the legal condition of the illegitimate both in Secular and Canon Law. In the end, using the documentary analysis of Letters of Legitimation, it was possible to compare the data obtained through bibliographic research, with the data raised from the manuscripts, and see how, in fact, the procedure of legitimization by royal grace worked and what were the common consequences. Finally, the conclusion was that the legal status of the sacrilegious offspring in Colonial Law had a flexible character, which reflected the secular and ecclesiastical institutional tolerance with illicit unions between priests and single women, allowing the social insertion of their bastards. by granting them inheritance rights and noble status.